الحركة المتجانسة في نموذج بيانكي من النوع الخامس في هندسة ليرا - الصباغ ف; عبد البصير ف; مصطفى ح (مجلة العلوم الطبيعية و الحياتية والتطبيقية, 2017)
In this paper we study a homothetic vector field of a Bianchi type-V model based on Lyra geometry. The aim of this paper is to get the components of homothetic vector field in Lyra geometry for Bianchi type-V, compare between it and the case of Bianchi type-I. Using ordinary method and Computer program to get the components of the vector . The results are compatible in the two methods and get the condition that the results tends to the case of Bianchi type-I. The cases when a displacement vector is a function of t and when it is constant are considered. In both two cases we investigate the equation of state.